2019
DOI: 10.22159/ijpps.2020v12i2.35415
|View full text |Cite
|
Sign up to set email alerts
|

Rp-HPLC and Chemometric Methods for the Determination of Two Anti-Diabetic Mixtures; Metformin Hydrochloride-Canagliflozin and Metformin Hydrochloride-Gliclazide in Their Pharmaceutical Formulation

Abstract: Objective: To develop and validate novel more sensitive analytical methods for the concurrent quantification of metformin-canagliflozin and metformin-gliclazide in their bulk forms and in their pharmaceutical preparations. Methods: Two methods were developed based on several chemometric assisted spectrophotometric methods and a Reversed-Phase High-Performance Liquid Chromatography (RP-HPLC). The first method applies different spectrophotometric chemometric assisted methods, including ratio difference, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…A thorough literature survey disclosed that several analytical and bioanalytical method development and validation reports were available for the assay of Metformin and Gliclazide simultaneously using ultraviolet (UV) spectrophotometry in bulk and formulations [14,15], High-Performance Liquid Chromatography (HPLC) in bulk and formulations [16][17][18][19][20][21], High-performance Thin-layer chromatography (HPTLC) in bulk and formulation [22], and HPLC in biological fluids [23]. However, there was no sufficient information reported elsewhere in the literature for the simultaneous determination of Metformin and Gliclazide in bulk and their fixeddose formulations using UPLC.…”
Section: International Journal Of Applied Pharmaceuticsmentioning
confidence: 99%
“…A thorough literature survey disclosed that several analytical and bioanalytical method development and validation reports were available for the assay of Metformin and Gliclazide simultaneously using ultraviolet (UV) spectrophotometry in bulk and formulations [14,15], High-Performance Liquid Chromatography (HPLC) in bulk and formulations [16][17][18][19][20][21], High-performance Thin-layer chromatography (HPTLC) in bulk and formulation [22], and HPLC in biological fluids [23]. However, there was no sufficient information reported elsewhere in the literature for the simultaneous determination of Metformin and Gliclazide in bulk and their fixeddose formulations using UPLC.…”
Section: International Journal Of Applied Pharmaceuticsmentioning
confidence: 99%
“…While MET along with its two impurities; CG (related compound A) [7] and ML (related compound D) [7] was determined by different methods [7,8,14,15]. Both CN and MT were determined together either in pharmaceutical formulations or biological fluids by different analytical methods as well [9,[16][17][18][19][20] also, an HPLC-diode array detection stability study for CN and MT determination in dosage forms was reported at which the forced degradation products were separated from both drugs without their quantification or chemical structure elucidation [21]. The literature survey showed no reported analytical method for the determination of CN, MT, their respective major degradation products DG and CG along with MT toxic impurity, ML.…”
Section: Introductionmentioning
confidence: 99%